Comparative Regulatory Models for MSME Financial Contract Protection in Indonesia and Philippines - Rizha Claudilla Putri; Erisa Ardika Prasada; Moulyta Elgi Trinanda (Walisongo Law Review (Walrev), 2026)
This article explores the legal protections available to Micro, Small, and Medium Enterprises (MSMEs) when entering contractual relationships with Financial Service Providers (FSPs) in Indonesia and the Philippines. The study departs from the recurring problem of unequal bargaining positions and the widespread use of standard-form contracts that limit MSMEs' ability to negotiate essential terms. Using a normative legal method supported by statutory analysis and a comparative approach, the research examines the principal regulatory instruments in both jurisdictions—Indonesia's OJK Regulation No. 22 of 2023 and the Philippines' Republic Act No. 11765. The discussion focuses on contractual principles, duties related to market conduct, transparency obligations, and the mechanisms available for consumer protection and enforcement. The comparison demonstrates that Indonesia's regulatory framework emphasizes preventive safeguards, while the Philippines adopts a more assertive model that combines remedial measures, adjudicatory powers, and stronger consumer-oriented guarantees. The findings suggest that Indonesia could enhance its system by reinforcing principle-based supervision, improving suitability assessments, and strengthening its dispute-resolution framework. Through this analysis, the article contributes to ongoing debates on how ASEAN countries might align their approaches to MSME protection in financial contracting. Artikel ini mengeksplorasi perlindungan hukum yang tersedia bagi Usaha Mikro, Kecil, dan Menengah (UMKM) ketika menjalin hubungan kontraktual dengan Penyedia Jasa Keuangan (LKM) di Indonesia dan Filipina. Studi ini berangkat dari masalah yang berulang mengenai posisi tawar yang tidak setara dan penggunaan luas kontrak standar yang membatasi kemampuan UMKM untuk menegosiasikan ketentuan-ketentuan penting. Dengan menggunakan metode hukum normatif yang didukung oleh analisis undang-undang dan pendekatan komparatif, penelitian ini mengkaji instrumen regulasi utama di kedua yurisdiksi—Peraturan OJK Indonesia No. 22 Tahun 2023 dan UU Republik Filipina No. 11765. Diskusi berfokus pada prinsip-prinsip kontraktual, kewajiban terkait perilaku pasar, kewajiban transparansi, dan mekanisme yang tersedia untuk perlindungan dan penegakan hukum konsumen. Perbandingan menunjukkan bahwa kerangka regulasi Indonesia menekankan perlindungan preventif, sementara Filipina mengadopsi model yang lebih tegas yang menggabungkan tindakan perbaikan, kewenangan peradilan, dan jaminan yang lebih berorientasi pada konsumen. Temuan menunjukkan bahwa Indonesia dapat meningkatkan sistemnya dengan memperkuat pengawasan berbasis prinsip, memperbaiki penilaian kesesuaian, dan memperkuat kerangka penyelesaian sengketa. Melalui analisis ini, artikel ini berkontribusi pada perdebatan yang sedang berlangsung tentang bagaimana negara-negara ASEAN dapat menyelaraskan pendekatan mereka terhadap perlindungan UMKM dalam kontrak keuangan. Keywords: MSME legal protection; standard-form contracts, market conduct regulation.